Comparing the Effectiveness of Stereo Projection vs 3D TV in Inducing Self-Motion Illusions (Vection) - Jordan, Jacqueline D.; Prpa, Mirjana; Feuereissen, Daniel; Riecke, Bernhard E. (ACM Symposium on Applied Perception SAP, 2014)
A necessary part of developing effective and realistic Virtual Reality (VR) simulations is emulating perceptual sensations that occur to humans in corresponding natural environments. VR users are often seated and unable to freely move through the virtual world, therefore necessitating other means to simulate and perceive self-movement. One approach to tackle this challenge is to induce embodied illusions of self-motion ("vection") in stationary observers, typically by providing moving visual stimuli on a wide field-of-view display. While numerous stimulus parameters have been shown to affect vection [see Riecke, 2011 for a review], there is little research investigating how the type of display itself might contribute. Here, we compared the vection-inducing potential as well as user experience and usability of two common displays for large-field stimulation: A passive stereoscopic projection setup and a 3D television with shutter glasses. Uncovering differences in vection between these displays would contribute to the theoretical understanding of vection and the potential relevance of different display properties, and guide the development of more immersive and effective VR setups. From a practical standpoint, this study helps to determine whether the more expensive projection system provides a benefit over the more accessible and affordable 3D television.
Keywords: Riecke; Riecke_2014; bernhard-riecke; conferencePapers; daniel-feuereissen; jacqueline-jordan; mirjana-prpa